1978
DOI: 10.1152/jappl.1978.44.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Familial aspects of decreased hypoxic drive in endurance athletes

Abstract: One difference between endurance athletes and nonathletes is decreased ventilatory responsiveness to hypoxia and hypercapnia. It has never been clear whether these decreased responses are a consequence of conditioning or precede participation in endurance athletics. Recent studies demonstrating clusters of decreased ventilatory responses to hypoxia in families of patients with unexplained respiratory failure suggest that decreased responses in endurance athletes might be familial. To investigate this possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 0 publications
6
40
0
Order By: Relevance
“…In studies of' patieints with unexplained respiratory f;ailure in wlhom ventilatory responses to hypoxia were found to be decreased, similarly decreased responses were found in healthy f;amily members (4,5). Furthermore, Saunders et al have shown a correlation between hypereapnic ventilatory responses seeni in championship swimmers and their siblings (9), and we have found decreased hypoxic ventilatory responses in successf'tul endurance runners and in their nonathletic parents and siblings (10).…”
Section: Introductionsupporting
confidence: 73%
“…In studies of' patieints with unexplained respiratory f;ailure in wlhom ventilatory responses to hypoxia were found to be decreased, similarly decreased responses were found in healthy f;amily members (4,5). Furthermore, Saunders et al have shown a correlation between hypereapnic ventilatory responses seeni in championship swimmers and their siblings (9), and we have found decreased hypoxic ventilatory responses in successf'tul endurance runners and in their nonathletic parents and siblings (10).…”
Section: Introductionsupporting
confidence: 73%
“…Reasons behind the varied performance response to LHTL training are probably multi-factorial however genetics may play a large part [38]. Studies have shown that a transcriptional factor, called a hypoxia-inducible factor (HIF), is essential in promoting cellular adaptation to changes in oxygen availability and regulating the hypoxic gene expression [39].…”
Section: Subjective Variablesmentioning
confidence: 99%
“…Med Scoggin et al 1978), but it is not yet certain whether hypercapnic ventilatory response is changed by physical trainig. In fact, the ventilatory response to hypercapnia after training has been reported to be decreased (Blum et al 1979), unchanged (Bradley et al 1980;Hughson 1980) and increased (Kelley et al 1984) as compared with pretraining.…”
Section: Expmentioning
confidence: 99%